Homicide and the Opioid Epidemic: A Longitudinal Analysis - Rosenfeld, Richard (Homicide studies, 2023)
Recent cross-sectional research has disclosed a positive relationship between opioid-related death rates and homicide rates. The current study adds a longitudinal dimension to this research. We estimate fixed effects panel models of the temporal relationship between race-specific homicide rates and opioid-related death rates within U.S. counties and county clusters between 1999 and 2015. The results reveal a positive association between change over time in homicide and opioid-related deaths, net of multiple socioeconomic and demographic controls, in both the Non-Hispanic White and Black population. The association is stronger in the Appalachian counties, where the opioid epidemic has been particularly severe.